Identification of primary and secondary UBA footprints on the surface of ubiquitin in cell‐mimicking crowded solution. Issue 7 (19th March 2017) - Munari, Francesca; Bortot, Andrea; Zanzoni, Serena; D'Onofrio, Mariapina; Fushman, David; Assfalg, Michael
Abstract : Despite significant advancements in our understanding of ubiquitin‐mediated signaling, the influence of the intracellular environment on the formation of transient ubiquitin‐partner complexes remains poorly explored. In our work, we introduce macromolecular crowding as a first level of complexity toward the imitation of a cellular environment in the study of such interactions. Using NMR spectroscopy, we find that the stereospecific complex of ubiquitin and the ubiquitin‐associated domain (UBA) is minimally perturbed by the crowding agent Ficoll. However, in addition to the primary canonical recognition patch on ubiquitin, secondary patches are identified, indicating that in cell‐mimicking crowded solution, UBA contacts ubiquitin at multiple sites. Abstract :